Modular Synthesis of Nona‐Decasaccharide Motif from Psidium guajava Polysaccharides: Orthogonal One‐Pot Glycosylation Strategy. Issue 19 (17th March 2020) - Zhang, Yunqin; Chen, Zixi; Huang, Yingying; He, Shaojun; Yang, Xingkuan; Wu, Zhibing; Wang, Xiufang; Xiao, Guozhi
Abstract: The synthesis of long, branched, and complex carbohydrate sequences remains a challenging task in chemical synthesis. Reported here is an efficient and modular one‐pot synthesis of a nona‐decasaccharide and shorter sequences from Psidium guajava polysaccharides, which have the potent α‐glucosidase inhibitory activity. The synthetic strategy features: 1) several one‐pot glycosylation reactions on the basis of N ‐phenyltrifluoroacetimidate (PTFAI) and Yu glycosylation to streamline the chemical synthesis of oligosaccharides, 2) the successful and efficient assembly sequences (first O3′, second O5′, final O2′) toward the challenging 2, 3, 5‐branched Ara f motif, 3) the stereoselective 1, 2‐ cis ‐glucosylation by reagent control, and 4) the convergent [6+6+7] one‐pot coupling reaction for the final assembly of the target nona‐decasaccharide. This orthogonal one‐pot glycosylation strategy can streamline the chemical synthesis of long, branched, and complicated carbohydrate chains. Abstract : A nona‐decasaccharide from Psidium guajava polysaccharides has been prepared in a modular one‐pot approach. The strategy features: 1) several one‐pot glycosylation reactions on the basis of N ‐phenyltrifluoroacetimidates (PTFAI) and Yu glycosylation, 2) the assembly sequences toward the 2, 3, 5‐highly branched Ara f motif, 3) the stereoselective 1, 2‐ cis ‐glucosylation, and 4) a final, convergent [6+6+7] one‐pot coupling reaction.